Status vaksinasi dengan kejadian stunting pada anak di bawah tiga tahun - Andri Yulianto; Yusnita Yusnita (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2022)
Background: Stunting conditions at birth affect the development or growth of children so stunting toddlers in the future will have difficulty in achieving optimal physical and cognitive development.Purpose: To determine the relationship between vaccination status and stunting occurrence among toddlers 1-3 years oldMethod: Observational analytic research with a case-control study approach. The sampling technique used is simple random sampling with a total sample of 99 respondents. Data collection uses an observation sheet on the Child's Identity Card (CIC). Statistical analysis using the Chi-Square Statistical Test.Results: From 33 toddlers 1-3 years old, there were 19 (57.6%) respondents who experienced stunting with a history of vaccination status in the incomplete category and 14 (42.4%) complete respondents. there is a relationship between vaccination status and the incidence of stunting in toddlers aged 1-3 years, the p-value is 0.011 (smaller than alpha = 0.05).Conclusion: There is a relationship between vaccination status and the incidence of stunting in toddlers aged 1-3 years in the work area of the Wates Health Centre.Keywords: Vaccination; Stunting; Toddler under 3 years oldPendahuluan: Kondisi stunting saat lahir berpengaruh terhadap perkembangan atau pertumbuhan anak sehingga batita stunting di masa datang akan mengalami kesulitan dalam mencapai perkembangan fisik dan kognitif yang optimal.Tujuan: Untuk mengetahui hubungan status imunisasi dengan kejadian stunting.Metode: Penelitian observational analitik dengan pendekatan studi kasus control. Teknik sampling yang digunakan yaitu simple random sampling dengan jumlah sampel yaitu 99 responden. Pengumpulan data menggunakan lembar observasi pada Kartu Identitas Anak (KIA). Analisis statistik menggunakan Uji Statistik Chi Square. Hasil: Diketahui dari 33 batita 1-3 tahun didapatkan yang mengalami stunting dengan riwayat status vaksinasi dalam kategori tidak lengkap sebanyak 19 (57,6%) responden dan lengkap 14 (42,4%) responden. ada hubungan status vaksinasi terhadap kejadian stunting pada batita 1-3 tahun diperoleh nilai p sebesar 0,011 (Lebih kecil dari nilai alpha = 0,05).Simpulan: Ada hubungan status vaksinasi terhadap kejadian stunting pada batita usia 1-3 tahun di wilayah kerja Puskesmas Wates.